Projeto Para Ela, Por Elas, Por Eles, Por Nós: opiniões e atitudes de profissionais acerca da atenção à mulher em situação de violência, em 10 municípios brasileiros - Elizangela Goncalves de Souza (2016)
The Atenção Integral à Saúde da Mulher em Situação de Violência: Para Elas, Por Elas, Por Eles, Por Nós, [Comprehensive Health (care) Services for Women in Gender Violence Situation: For them (women) known, it is nationwide and is being carried out by the Health and Peace Promotion Center of Social and Preventive Medicine Department of School of Medicine of Universidade Federal de Minas Gerais [Federal University of Minas Gerais] (UFMG), through the Professional Masters in Promotion of Health and Prevention of Violence, with technical and financial support of Ministério da Saúde [Ministry of Health] (MS). This major woman approach project in violence situations has, as one of its objectives, to contribute to the Política Nacional de Atenção Integral à Saúde da Mulher [National Policy of Integral Care to Women's Health], with strategic actions (PNAISM) and to the Pacto Nacional de Enfrentamento da Violência Contra a Mulher [National Pact of Violence Against Women]. One of the Project goals is the organization of services and staff in priority municipalities, headquarters of Citizenship Territories, distributed in the five Brazilian macroregions, which were defined, in 2011, by the Permanent National Forum to Deal with Violence Against the Rural and Forest-based Women, represented by Secretaria de Política para as Mulheres [Secretariat of Policy for Women] (SPM), the MS and Social Movements of Women, besides other organs. To accomplish this goal for the Para Elas Project, in addition to other activities, local workshops in each of the municipalities, involving professionals of the network of care to women in situations of violence were held. Due to my involvement with the project, I had more contact with issues related to public policies of women's health, gender relations and violence against women. Since 2013, I have participated in weekly meetings, I am part of the Organizing Committee of the workshops and I work as a collaborator and researcher of theoretical and methodological definition activities, data analysis and field research. As a Professional Master Degree's student of Health and Violence Prevention Promotion, my research project appears linked to the "Para Elas" where we sought to analyze the performance of the professionals involved in care for women in situations of violence in the 10 priority municipalities mentioned. The survey was conducted with all professional participants of the workshops, by means of semi-structured interviews, using self-administered questionnaires. Descriptive statistics, bivariate analysis, and finally, Correspondence analysis were used for data analysis. For the qualitative part, categorization of the transcribed speeches was first made, from which variables were generated, for which the frequency distribution was performed, and, in an articulated way, categories for content analysis. The results show that the number of professionals that assisted suspected cases is higher than the number of those who assisted confirmed cases of violence against women. However, less than half of the professionals, who assisted suspected cases, adopted some attitude towards them, there being a strong association between the care of these cases and attitudes to direct and discuss the case with the team. The adoption of some action by the professionals was more common - although well below half for most actions - before the confirmed cases, there being a strong association of their care with the family follow-up actions, follow-up and return schedule of women, as well as the approach. The underreporting occurs in both suspected cases and confirmed cases. The actions to be developed by the health sector for the prevention of violence against women, mentioned more frequently by respondents were orientation/information, professional training and investment in infrastructure services, with little mention of the actions that involve working with aggressor and the male public, as well as those aimed at women's empowerment. Most interviewed subjects think that it is the role of the health sector to develop actions to prevent violence against women, however, although all of them were in front position of responsibility to the care to women victims of violence, there was a high proportion of responses left blank or reporting lack of opinion on the matter. We conclude that the Attention to Women in Violence Situations is far from achieving being adequately supplied by the Network, as professionals routinely refer more than they approach or identify cases, continuing notifying little, they do not feel qualified, and, sometimes, they do not even see themselves as responsible for this attention.